Entropy, environment and resources: an essay in physico-economics - Faber, Malte; Niemes, Horst; Stephan, Gunter (Springer Berlin Heidelberg, 1987)
Long run aspects of environmental protection and of the use of resources areanalyzed within a planning model. To this end fundamental concepts of thermodynamics are explained in a simple manner. The relationships between entropy, energy necessary for the extraction of a resource and the concentration of the resource is employed to establish a connection between the economic systems and the environment